Hoysala temples. A Synthesis of Architecture and Sculpture - Vinokurova, Anastasia S. (Actual Problems of Theory and History of Art, 2025)
The present article is an investigation of complex unity of architecture and sculpture of Hoysala dynasty in the 11th—14th cc. There is an attempt to describe Vesara architectural typology which served as a basis for the formation of unique stellate temple plans achieving their full development under the Hoysala.
Keywords: Hoysala; Hindu architecture; sculpture; Vesara; South India